From tissue mechanics to transcription factors - Janmey, Paul A.; Wells, Rebecca G.; Assoian, Richard K.; McCulloch, Christopher A. (Differentiation (London), 2013)
Changes in tissue stiffness are frequently associated with diseases such as cancer, fibrosis, and atherosclerosis. Several recent studies suggest that, in addition to resulting from pathology, mechanical changes may play a role akin to soluble factors in causing the progression of disease, and similar mechanical control might be essential for normal tissue development and homeostasis. Many cell types alter their structure and function in response to exogenous forces or as a function of the mechanical properties of the materials to which they adhere. This review summarizes recent progress in identifying intracellular signaling pathways, and especially transcriptional programs, that are differentially activated when cells adhere to materials with different mechanical properties or when they are subject to tension arising from external forces. Several cytoplasmic or cytoskeletal signaling pathways involving small GTPases, focal adhesion kinase and transforming growth factor beta as well as the transcriptional regulators MRTF-A, NFκB, and Yap/Taz have emerged as important mediators of mechanical signaling.